Company Management in the Insurance Sector: Valuing Employees and their Work Commitment - Serrasqueiro , João; Félix , Marta; Veiga , Pedro; Ferreira , Paulo; Almeida , Dora (Journal of Ecohumanism, 2025)
This study focuses mainly on the role of employees in insurance companies in Portugal, analysing the importance of valuing them and their commitment to their work. Considering the above, this research aims to examine which aspects lead to greater commitment on the part of employees and what makes them feel valued within the organisations where they work. A quantitative methodology was used to fulfil this objective, and a questionnaire was applied to various employees in the insurance companies operating in the Portuguese market. The study’s results of the study highlight a positive relationship between leadership, the inclusion of employees, and their commitment to work. They also highlight that participation in decision-making positively influences their satisfaction, appreciation, and loyalty to their company. It can, therefore, be concluded that investing in employees and increasing their satisfaction and commitment is crucial for sustainable growth and organisational success.